Stabilization policy in an open-economy equilibrium model - Ulrich Lächler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
Whether the interests of a nation are best served by maintaining fixed exchange rates or by allowing exchange rates to vary continues to be a much debated issue among economists. Most of the earlier literature on this topic focused attention on the two extremes of completely fixed exchange rates versus the perfectly flexible or free floating system, examining the circumstances (degree of factor mobility, structure and origin of disturbances, etc.) under which one or the other would be preferred. More recently, several authors have adopted a different perspective by which the fixed and free float regimes are considered endpoints on a continuous spectrum of exchange rate flexibility (e.g. Boyer (1978), Frenkel and Aizenman (1982), Roper and Turnovsky (1980)). Undoubtedly, this view was stimulated by the move toward a system of managed floating among the major world currencies since 1973, where governments intervene in foreign exchange markets to varying extents, but not enough to peg the exchange rate.
Keywords: 330